Toward Ecological Justice: A Maqāṣid-Based Socioeconomic Analysis of Coastal Reclamation in Tapakerbau, Indonesia - Taufiq, M.; Suaidi, Suaidi; Abdillah, Kudrat (UIN Sunan Kalijaga, 2025)
This study investigates the academic challenge of reconciling economic development with ecological sustainability in the context of coastal reclamation in Tapakerbau, Sumenep, Indonesia—a process that has generated social conflict, environmental degradation, and distributive injustice. Utilizing the maqāṣid framework, the research employs a qualitative socio-legal methodology, incorporating in-depth interviews, field observations, and analysis of legal documents alongside a review of literature on Islamic environmental jurisprudence (fiqh al-bī'ah). The findings reveal that, despite the brief duration of the reclamation project, it resulted in initial ecological damage, restricted fishermen’s access to coastal resources, and reinforced the dominance of local political and economic elites. This study emphasizes the significance of environmental preservation (ḥifẓ al-bī'ah) as a fundamental objective within the framework of maqāṣid discourse, particularly in the context of contemporary ecological challenges. It highlights the imperative for coastal development models that are inclusive, participatory, and ecologically equitable. Practically, the Tapakerbau case provides a crucial lesson for environmental conservation in Indonesia, emphasizing the importance of addressing sustainable development and environmental justice issues.